PAYMENT SYSTEM FOR OLD AGE SECURITY CLAIMS AT BPJS EMPLOYMENT OF MEDAN CITY BRANCH OFFICE - Melia br Ginting; Nuri Aslami (Transpublika Publisher, 2022)
The Old Age Security Program or usually called JHT is a protection program that is held with the aim of ensuring that participants receive cash when entering retirement, experiencing permanent total disability, or death. This study aims to find out what are the requirements that are attached when submitting an old-age security claim, the procedure for claiming an old-age security, the requirements for an old-age security claim, and obstacles or problems that occur during the old-age security claim process. This research was conducted at the BPJS Employment of Medan City branch office. In the research conducted, researchers used qualitative research to obtain results based on data that were searched, collected, processed, and analyzed to confirm the desired results. This study used two data sources, namely primary data and secondary data. The results showed that the payment of claims at BPJST employment of Medan City Branch Office has been maximized, fast in the process, on target, and on time. BPJS employment of Medan Branch Office has fulfilled the concept of fairness of distribution in the payment of claims, so as to provide a better quality of life for its participants. In accordance with the mission of BPJS, that the program aims to ensures the safety and prosperity of all workers and their families.